Gefitinib loaded nanostructured lipid carriers: characterization, evaluation and anti-human colon cancer activity in vitro. (1st January 2020) - Makeen, Hafiz A.; Mohan, Syam; Al-Kasim, Mohamed Ahmed; Attafi, Ibraheem M.; Ahmed, Rayan A.; Syed, Nabeel Kashan; Sultan, Muhammad Hadi; Al-Bratty, Mohammed; Alhazmi, Hassan A.; Safhi, Mohammed M.; Ali, Raisuddin; Intakhab Alam, M.
Abstract: NLC containing Gefitinib (NANOGEF) was prepared using stearic acid, sesame oil and surfactants (sodium lauryl sulfate and tween 80). NANOGEFs were evaluated for particle size, polydispersity index (PdI), zeta potential, entrapment efficiency (EE), stability, release studies and cytotoxicity studies (MTT assay). The optimized NANOGEF exhibited particle size of 74.06 ± 9.73 d.nm, PdI of 0.339 ± 0.029 and EE of 99.76 ± 0.015%. The TEM study revealed spherical shape of NANOGEF formulations. The slow and sustained release behavior was exhibited by all NANOGEFs. The effects of surfactants were observed not only on particle size but also on zeta potential, entrapment efficiency, stability and release studies. The MTT assay revealed 4.5 times increase in cytotoxicity for optimized NANOGEF (IC50 = 4.642 µM) when compared with Gefitinib alone (IC50 = 20.88 µM in HCT-116 cells). Thus NANOGEF may be considered as a potential drug delivery system for the cure of colon cancer.